About “supramanzanas” in the architecture of the city - Sáenz Guerra, Javier (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2014)
In the evolution of the city, beautiful buildings are losing functional qualities during the passage of long periods of its history. End, in some cases, becoming impassable urban barriers. At the same time, municipal decisions with enormous ambition, proposed new buildings whose size will determine the shape of the city. In some examples, we will develop a miscellany of situations in which architects fine job they have learned to use the geometry needed in large urban infrastructure to improve the way the City. Also is worth noting the use of the Empty as shaping of urban space in this new construction. From interventions in some way in the actuality, as in the example of Milan Zaha Hadid in City Life, or spaces frozen in time, as the Conde Duque building in Madrid, insert numerous cases that contribute to the formation of a criterion plastic, from a personal standpoint.